Preserving Tawheed Among Patani Youth Activists: Exploring the Role of Ethno-Religious Identity in Resisting Systematic Oppression - Abadi, Mansurni; Wulandari, Wulandari; Golasila, Ana Octavia (Pusat Pengkajian dan Pengembangan Islam Jakarta (PPIJ), 2024)
The ongoing conflict between thai goverment and Malay-muslim insurgents has made thailand deep south consist of pattani, yala, and narathiwat province within with four district in songkla Province one of the most volatile region in ASEAN. While there is evidence if their struggle influence by transnational jihadist movement, but sense of ethno-religious existed much longer. Malay-muslim population in thailand deep south, construct their identity based on intersection between Religion and Ethnic- Vice versa. using qualitative method, with combination three theory , identity development, ethno-religious, and resistance studies. this research try to explore how ethno-religious function , especially among youth to keeeping resistance alive beside perserve identity as malay and Muslim in Thai-budhis society. we found ethnoreligious become tools of resistance with five ways and strenghten tawheed in face of systematic oppresion.